Exploring MRI Safety Knowledge Among Physicians and Nurses in Saudi Arabia: Highlighting Knowledge Gaps and Key Influencing Factors - Ibrahem Hussain Kanbayti (Journal of Medical Radiation Sciences)
ABSTRACT Introduction Magnetic resonance imaging (MRI) is a widely used diagnostic modality in healthcare settings, but it carries inherent safety risks. Understanding healthcare providers' knowledge of MRI safety is crucial for ensuring patient and staff safety. This study aimed to assess MRI safety knowledge among physicians and nurses and explore factors influencing this knowledge. Methods A cross‐sectional study was conducted among 387 nonimaging healthcare practitioners: physicians and nurses, from different healthcare sectors in Jeddah city. A structured questionnaire assessed their understanding of basic MRI concepts, projectile hazards and contrast media risks. Statistical analyses, including Student's t‐test and ANOVA, were used to examine differences in knowledge scores. Results Participants showed limited or poor knowledge across all MRI safety domains, including basic concepts, projectile hazards and contrast media risks, with domain knowledge scores of 31.8%, 33.7% and 32.3%, respectively. Factors having an impact on knowledge of MRI safety were the type of healthcare sector, qualification, work experience, attending workshops and whether the education curriculum included MRI safety (p ≤ 0.05). Conclusions The study highlighted substantial deficits in MRI safety knowledge among nonimaging healthcare practitioners: physicians and nurses. Addressing these gaps through targeted education and training programs is essential for improving patient and staff safety in MRI settings.